Analysis of Community Empowerment Through the Earth Alms Tradition in Cantigi Kulon Village, Cantigi District, Indramayu Regency - Siti Juhrotun Hasanah (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
The tradition of "sedekah bumi" (earth alms) is a cultural heritage deeply rooted in the lives of the people of Cantigi Kulon Village, Cantigi District, Indramayu Regency. This study aims to analyze the role of this tradition in community empowerment across various aspects, including socio-cultural, economic, spiritual, and environmental aspects. The method used was a qualitative approach with a case study design, through in-depth interviews, participant observation, and thematic analysis. The results indicate that "sedekah bumi" (earth alms) is not only a means of expressing gratitude to God for the harvest but also strengthens ties between residents, increases income through local economic activities, strengthens religious values and character, and fosters awareness of environmental protection. This tradition demonstrates that local wisdom can be a driving force for sustainable community empowerment.